Epidermal studies of three species of Vernonia Schreb. in Southern Nigeria - CATHERINE IJEOMA KEMKA EVANS; BOSA OKOLI; CHIB UIKE NWACHUKWU (Biodiversitas Journal of Biological Diversity, 2014)
Kemka-Evans CI, Okoli B, Nwachukwu CU. 2014. Epidermal studies of three species of Vernonia Schreber in Southern Nigeria. Biodiversitas 15: 137-141.The leaf epidermal studies of three species of Vernonia namely V. cinerea (L) Less, V. amygdalina Delile.(bitter leaf and non-bitter leaf variety) and V. conferta Benth. were undertaken with the aim of revealing their foliar characters whichwill enhance their identification and determination of their taxonomic relationship. Matured leaves were soaked in Sodium OxochlorateII for 24hours to separate the epidermal surfaces. Data from the measurement of stomata and epidermal cells were analyzed. Thepresence of diagnostic characters such as contiguous stomata and sinuous anticlinal walls on the abaxial leaf surface of non-bitter varietyof V. amygdalina and on both leaf surfaces (adaxial and abaxial) of V. cinerea are of taxonomic importance. The irregular T-shapedtrichomes on the leaf surfaces of V. amygdalina (bitter leaf) and the cuticular striations on the adaxial surface of the same taxa could beused to delimit the taxa from the other species. The distribution of the stomata show hypoamphistomatic in all the three species studied.Anomocytic stomata occurred on all the taxa studied. Anisocytic stomata were found on the abaxial surface of V. conferta. Thesecharacters examined revealed interspecies relationship among the three species and also suggest that V. amygdalina (non bitter leaf) is avariety of V. amygdalina (bitter leaf) and should not be regard as another species of Vernonia. The epidermal leaf characters of V. amygdalina (non-bitter leaf) is also been reported for the first time.